Educational robotics and the use of drones in education: a systematic mapping of the literature (Research, Society and Development, 2022)
Educational Robotics and the use of drones in education have become increasingly popular in recent years. This is mainly due to the possibilities that these tools have, when used in harmony, a greater ability to engage students in understanding subjects such as mathematics and physics. Thus, it can be seen that educational robotics and the use of drones in education can contribute to the potential, scientific, and technological development of students. This study aimed to perform a systematic mapping of the existing literature in Portuguese language published in the last five years (2018-2022) on the theme: Educational Robotics and use of drones in Education. This qualitative and descriptive research used as technical procedure a systematic mapping of literature. It is a secondary research that aimed to identify and select the publications on Educational Robotics and Use of Drones in Education. The study consulted two digital platforms of great importance to the academic community, the National Digital Library of Theses and Dissertations (BDTD) and the Capes Periodical Portal. The research covered the period from 2018 to 2022, seeking to identify the existing productions on these platforms, as well as to identify possible gaps on the researched theme. Once the search strategies were defined and applied, 20 documents were initially found, including articles, dissertations, and theses, of which 5 were selected for their direct relevance to the research questions being addressed here.